2011
DOI: 10.1039/c0cp01856b
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond X-ray absorption measurements of the ligand substitution dynamics of Fe(CO)5 in ethanol

Abstract: Ultrafast X-ray absorption near edge spectroscopy has been carried out for photo excited iron pentacarbonyl in ethanol with 2 picosecond resolution. A temporal resolution limited dissociation process was observed, followed by the formation of the mono-substituted complex Fe(CO)(4)EtOH within a few tens of picoseconds. The measurements have been carried out with a newly developed X-ray absorption instrument at station 7 ID-C of the Advanced Photon Source. The results show that single picosecond temporal resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 58 publications
3
42
0
Order By: Relevance
“…An important aspect of the reactivity of the latter relates to its spin state. 252,253 Using timeresolved Fe K-edge X-ray absorption spectroscopy with a plasma source, Ahr et al 256 investigated Fe(CO)5 photodissociation in ethanol and concluded that due to electronic interaction with the solvent molecules, the removal of CO and the addition of EtOH were concerted processes, although the Fe(CO)4EtOH product was not resolved directly. Their model was based on the argument that in solution a weak Fe(CO)5-EtOH complex is formed in the ground state.…”
Section: Fe(co)5mentioning
confidence: 99%
“…An important aspect of the reactivity of the latter relates to its spin state. 252,253 Using timeresolved Fe K-edge X-ray absorption spectroscopy with a plasma source, Ahr et al 256 investigated Fe(CO)5 photodissociation in ethanol and concluded that due to electronic interaction with the solvent molecules, the removal of CO and the addition of EtOH were concerted processes, although the Fe(CO)4EtOH product was not resolved directly. Their model was based on the argument that in solution a weak Fe(CO)5-EtOH complex is formed in the ground state.…”
Section: Fe(co)5mentioning
confidence: 99%
“…[20][21][22][23][24] More recently, ultrafast studies on the photochemistry of Fe(CO) 5 in solution have been pushed into the x-ray domain and an Fe K-edge x-ray absorption study was reported by Rose-Petruck and co-workers, 25 while Wernet et al 26,27 implemented femtosecond Fe L 3 -edge resonant inelastic xray scattering (RIXS) at the x-ray Free Electron Laser in Stanford. RIXS, which is a variant of x-ray emission spectroscopy, is a sensitive probe of the spin state of molecular systems.…”
Section: Introductionmentioning
confidence: 99%
“…Short light pulses in the extreme ultraviolet (XUV) range find a wide variety of applications in studies on electronic and structural dynamics of molecules and molecular complexes [1][2][3]. In particular, photoelectron spectroscopy with the use of XUV radiation is a powerful method to probe the electron density in a valence shell of a molecular system.…”
Section: Introductionmentioning
confidence: 99%